Multmode microscopy to probe bacteria surface interactions - Ison, Elizabeth (2025)
The formation of biofilms in healthcare can have disastrous effects. Biofilms are intrinsically more tolerant to antimicrobials than individual cells which therefore makes biofilm infections more difficult to treat. To overcome this, strategies to prevent biofilm formation are required. Here, imaging methods and data analysis pipelines are designed to find new information regarding the impact of antimicrobials on motility and biofilm-resistant surfaces. Antimicrobials adsorbed on dental and other surfaces are suggested to delay biofilm formation and have been shown to kill bacteria. To obtain new insights into the impact of antimicrobial adsorbed surfaces on the motility of Pseudomonas aeruginosa, a selection of soluble compounds are considered; chlorhexidine (CHX), cetylpyridinium chloride (CPC), isopropyl methyl phenol (IPMP), and a formulation of CHX (fCHX). A digital holographic microscopy (DHM) model was used to investigate the live in vitro 3D motility of P. aeruginosa in response to the antimicrobials adsorbed to glass surfaces. Changes in motility were observed and quantified when early exponential phase P. aeruginosa cells were exposed to CHX and fCHX. Late exponential phase fCHX-exposed cells had fewer motile cells and increased tortuosity within 12 min. The lack of late exponential phase P. aeruginosa motility changes in response to the CHX-adsorbed surface suggests a growth-phase-dependent resistance. This growth-phase dependent resistance is suggested to be mediated by RpoS as a P. aeruginosa mutant deficient in RpoS showed motility changes at late exponential phase with CHX exposure. IPMP and CPC adsorbed surfaces did not induce motility changes in P. aeruginosa. The attachment of P. aeruginosa to surfaces adsorbed with antimicrobials did not correspond to the motility changes. The DHM motility model was also developed to allow for the interrogation of how antimicrobials in mouthwashes impact the motility of orally relevant bacteria. X-ray photoelectron spectroscopy (XPS) of CHX adsorbed to glass and enamel suggests the glass model is an underrepresentation of adsorption in the oral cavity whereas CPC adsorption is suggested to be an overrepresentation. Motile, orally relevant bacteria (Campylobacter rectus and Treponema denticola) were selected and exposed to the adsorbed glass surfaces. DHM of C. rectus showed a change in motility with exposure to CHX, CPC, and fCHX. No changes were seen in the motility of T. denticola however DHM tracking of spirochetes requires further development. As with the P. aeruginosa model, the motility of bacteria did not correspond with surface attachment. Microtopographies have previously been found to reduce biofilm formation and are investigated here using surface cell tracking to elucidate the mechanism by which topographies interfere with biofilm formation. Previous work showed bacterial attachment at 4 h was dependent on the spacing between 10 µm tall pillars. A differential interference contrast (DIC) video microscopy imaging and analysis pipeline was developed to track bacterial swimming motility over these complex topographies. The development of the tracking methodology highlights a confinement mechanism whereby the transition from reversible to irreversible attachment is interrupted. This is suggested to be through the topographies causing localised accumulation of quorum sensing molecules which induce early rhamnolipid production. These biosurfactant rhamnolipids are thought to prevent the transition to irreversible attachment and therefore stop the surface attachment of P. aeruginosa. Here, the use of DHM and DIC microscopy allowed for the interrogation of bacterial motility. DHM of bacteria responding to antimicrobial adsorbed surfaces suggests the growth-phase development resistance to antimicrobials. The use of DIC microscopy to investigate motility across topographical surfaces highlights a previously unappreciated confinement mechanism which suggests the ability of surfaces to modulate bacterial attachment.